The impact of government agricultural input support programme in promoting food security in Zimbabwe: a case study of Mazowe district - Chikengezha, Audrey (Midlands State University, 2017)
Food security has remained a very big challenge in many rural areas in Zimbabwe. Many households in the country’s rural areas have remained impoverished in terms of food security. Maize being a strategic grain crop for food security and livelihood purposes for the nation has remained low in production amongst smallholder farmers in the country. The government of Zimbabwe has realized the importance of maize production and implemented the input support programme to boost agricultural production so as to promote food security for households and the nation at large. However, household food security prospects are under threat due to continuous decline in maize production especially in the smallholder farming sector that is regarded as the major producers of maize grain. Among other factors, low maize production is blamed on the ineffectiveness of the programme and other natural factors beyond human control like climate change. Government interventions to reverse declining maize production and promote food security are mainly centered on subsidized input provisions but yields remain low. Apart from production gains realized from increased input usage, sustainable production gains can also be realized through efficient use of these resources